Advances and applications on non-Hermitian topological photonics - Yan Qiuchen; Zhao Boheng; Zhou Rong; Ma Rui; Lyu Qinghong; Chu Saisai; Hu Xiaoyong; Gong Qihuang (Nanophotonics)
Non-Hermitian photonics and topological photonics, as new research fields in optics, have attracted much attention in recent years, accompanying by a great deal of new physical concepts and novel effects emerging. The two fields are gradually crossed during the development process and the non-Hermitian topological photonics was born. Non-Hermitian topological photonics not only constantly produces various novel physical effects, but also shows great potential in optical device applications. It becomes an important part of the modern physics and optics, penetrating into different research fields. On one hand, photonics system can introduce artificially-constructed gain and loss to study non-Hermitian physics. Photonics platform is an important methods and ways to verify novel physical phenomena and promote the development of non-Hermitian physics. On the other hand, the non-Hermitian topological photonics provides a new dimension for manipulating topological states. Active and dissipate materials are common in photonic systems; therefore, by using light pump and dissipation of photonic systems, it is expected to promote further development of topological photonics in device applications. In this review article, we focus on the recent advances and applications on non-Hermitian topological photonics, including the non-Hermitian topological phase transition and skin effect, as well as the applications emerging prosperously in reconfigurable, nonlinear and quantum optical systems. The possible future research directions of non-Hermitian topological photonics are also discussed at the end. Non-Hermitian topological photonics can have great potential in technological revolution and have the capacity of leading the development of both physics and technology industry.